Deposition of mass-selected ions in neon matrices: CS2+ and C6 F6+: Low-Temperature Physics and Chemistry in Cryomatrice - Lorenz, Martin; Bondybey, Vladimir E. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2000)
Infrared, visible absorption as well as laser induced fluorescence (LIF) and excitation spectra are obtained for several simple cations deposited from a mass selected ion beam. In the present preliminary study we demonstrate the successfull and clean mass selection by presenting spectra of samples obtained by depositing the isotopic 34S12C32S+ ion in natural isotopic abundance, and analysing its spectrum. Spectra of C6F6+ deposited from a 20 eV ion beam exhibit quite different inhomogeneous line profiles, suggesting that even the relatively low kinetic energy results in considerable damage of the solid. Analysis of the spectra indicates that the Jahn√Teller distorted vibrational structure in the doubly degenerate ground state of C6F6+ is strongly perturbed in the newly formed sites, which are presumably of lower symmetry. A 33√46 cm-1 splitting of the origin and other totally symmetric bands in emission is tentatively attributed to the spin-orbit splitting in the 2E1g ground state.